Development and initial validation of a defensive pressure index using tracking data in the Chinese super league - Li, J.; Wu, F.; Li, A.; Martínez-Santos, R. (Frontiers in Sports and Active Living, 2026)
Tracking data have enhanced the analysis of football performance; however, defensive pressure remains insufficiently operationalised. This study aimed to develop a Defensive Pressure Index (DPI) based on movement tracking data, to examine its association with defensive outcomes, and to explore whether DPI differs across running score. Positional tracking data from 30 Chinese Super League matches during the 2018 season were analysed, yielding 2,032 defensive sequences. Defensive pressure was conceptualised as the degree of spatiotemporal constraint imposed on the attacking team during defensive sequences and was quantified using a composite index derived from six spatial tactical variables. Ordered logistic regression was used to examine the association between DPI and defensive outcomes, while one-way ANOVA was used to assess differences in DPI across running score. Higher DPI values were significantly associated with more favourable defensive outcomes (p < 0.001), providing preliminary evidence that the index captures meaningful sequence-level variation in defensive pressure. However, this finding should be interpreted with caution because the proportional odds assumption showed evidence of deviation. By contrast, DPI did not vary significantly across running score, suggesting that defensive pressure at the sequence level was more closely related to local spatial tactical organization than to scoreline alone. Overall, the DPI provides a transparent and replicable framework for quantifying defensive pressure in professional football. Future research should further evaluate the index using broader datasets and modelling approaches that account for the hierarchical structure of match data.